Sarcopenic obesity: epidemiology, pathogenesis and diagnostic criteria - S. A. Berns; A. F. Sheptulina; E. M. Mamutova; A. R. Kiselev; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Recently, two following demographic trends have been clearly observed in the world: population aging and an increase in the prevalence of obesity. In February 2022, the European Society for Clinical Nutrition and Metabolism (ESPEN) and the European Association for the Study of Obesity (EASO) published the first consensus guidelines for the definition and diagnosis of sarcopenic obesity, which characterizes by a combination of excess adipose tissue with a decrease in muscle mass, muscle strength and impaired muscle function. The purpose of this review is to describe the prevalence, the main etiopathogenetic factors of sarcopenic obesity, as well as currently accepted approaches to the diagnosis of this condition.